Perceived work-related stress and pain prevalence: results from the Italian CUPID study. (19th October 2011) - Conti, Marco; Coggon, David; Bertù, Lorenza; Landone, Stefano; Picinelli, Filippo; Veronesi, Giovanni; Bonzini, Matteo
Abstract : Objectives: To assess the importance of work-related stress among recognised risk factors in causing musculoskeletal disorders (MSDs). Methods: The CUPID standardised questionnaire was administered to 518 nurses employed in a large University Hospital in Varese (Italy) to collect MSK disorders in last month and related work-absence. We also collected self-perceived work-related stress through the two most internationally validate tools: the Job-Content and the Effort-Reward Imbalance questionnaires (ERI-Q and JC-Q respectively). Somatising tendency and Overcomittment were also investigated. Multivariate logistic regression, stratified by physical workload, was used to assess the association between outcomes and risk factors adjusted for age and sex. Results: Of the 410 collected questionnaire (participation rate=79%), low-back pain was reported by 50%, neck pain by 47% and shoulder pain by 33%. The two stress questionnaires showed high inter-correlation, with ERI resulting with a higher internal consistency. Considering pain prevalence, after controlling for age and sex, ERI-Q resulted associated to low-back and neck in the group who declared no exposure to heavy lifting (OR=1.48 IC 95%:1.11–1.99 and OR=1.22 IC 95%:1.04–1.44 respectively). JC-Q was associated only to a higher prevalence of shoulder pain in both groups (OR=1.91 IC 95%=1.02–3.59 among not exposed and OR=3.16 IC 95%=1.24–8.06 among exposed). Somatising tendency was associated to pain prevalence in all investigated districts, with higher ORs seen among patients not exposed to physical workload. Conclusions: Psychosocial factors such as perceived stress and somatising tendency resulted to be an important risk factor for MSD, besides to the already established ones. Results of 1-year follow-up will be also presented.